Formation of Au and tetrapyridyl porphyrin complexes in superfluid helium. Issue 26 (14th July 2015) - Feng, Cheng; Latimer, Elspeth; Spence, Daniel; Al Hindawi, Aula M. A. A.; Bullen, Shem; Boatwright, Adrian; Ellis, Andrew M.; Yang, Shengfu
<x xml:space="preserve">Abstract</x> Binary clusters have been formed by co-addition of 5, 10, 15, 20-tetra(4-pyridyl)porphyrin (H2TPyP) and gold atoms to helium nanodroplets, and the resulting complexes are found to have different structures at different pickup orders.